Increasing Public Awareness in Loving the Environment with a Flower Garden in Sanja Village - Akbar, Ananda Fauzan; Rinda, Rachmatullaily Tinakartika (Jurnal Pengabdian Nusantara, 2024)
This research is a form of community service to see the Increase of Community Awareness to Love the Environment with Flower Gardens in Sanja Village and the approach used in this study is a descriptive approach with a qualitative method, This research was carried out in RT 04 RW 02 Sanja Village, Citeureup District, Bogor Regency.  The result of the garden creation activities carried out in Sanja Village is to make a greening place and make residents love their environment even more, with the garden creation program, this becomes a greening and environmentally friendly place.